Homologie en hermeneutiek - Wethmar, C. J. (Hervormde teologiese studies, 1988)
Homology and henneneutics One of the issues in present-day systematic theology which requires urgent research is the nature of church doctrine. This article attempts a contribution in this regard by analysing the elements which the hermeneutical theology of Gerhard Ebeling could supply for a theological notion of doctrine. Referring to Ebeling's views on revelation, faith, church and human existence it is suggested that homology and hermeneutics are phenomena which are only adequately understood when they are seen as closely linked. Doctrine is the form which the understanding of Holy Scripture adopts when interpreted in the light of the presuppositions of a particular horizon of understanding.